Personalized genetics of the cholinergic blockade of neuroinflammation. (21st March 2017) - Simchovitz, Alon; Heneka, Michael T.; Soreq, Hermona
Abstract : We review the predicted cognitive and inflammation‐related impact of Single Nucleotide Polymorphisms (SNPs) in the acetylcholinesterase AChE gene. Specifically, microRNA regulators maintain balanced cognition‐inflammation state in the brain (left hand side). SNPs disrupting microRNA binding to AChE may exacerbate inflammation and impair cognition, or vice versa, which may therefore alter the response to anticholinesterase medications in Alzheimer's Disease treatment (right hand side). This is an article for the special issue XVth International Symposium on Cholinergic Mechanisms . Abstract: Acetylcholine signaling is essential for cognitive functioning and blocks inflammation. To maintain homeostasis, cholinergic signaling is subjected to multi‐leveled and bidirectional regulation by both proteins and non‐coding microRNAs ('CholinomiRs'). CholinomiRs coordinate the cognitive and inflammatory aspects of cholinergic signaling by targeting major cholinergic transcripts including the acetylcholine hydrolyzing enzyme acetylcholinesterase (AChE). Notably, AChE inhibitors are the only currently approved line of treatment for Alzheimer's disease patients. Since cholinergic signaling blocks neuroinflammation which is inherent to Alzheimer's disease, genomic changes modifying AChE's properties and its susceptibility to inhibitors and/or to CholinomiRs regulation may affect the levels and properties of inflammasome components such as NLRP3. This calls for genomic‐based medicine approaches based on genotyping of both coding and non‐coding single nucleotide polymorphisms (SNPs) in the genes involved in cholinergic signaling. An example is a SNP in a recognition element for the primate‐specific microRNA‐608 within the 3′ untranslated region of the AChE transcript. Carriers of the minor allele of that SNP present massively elevated brain AChE levels, increased trait anxiety and inflammation, accompanied by perturbed CholinomiR‐608 regulatory networks and elevated prefrontal activity under exposure to stressful insults. Several additional SNPs in the AChE and other cholinergic genes await further studies, and might likewise involve different CholinomiRs and pathways including those modulating the initiation and progression of neurodegenerative diseases. CholinomiRs regulation of the cholinergic system thus merits in‐depth interrogation and is likely to lead to personalized medicine approaches for achieving better homeostasis in health and disease. This is an article for the special issue XVth International Symposium on Cholinergic Mechanisms .